Efficient Ni‐based catalysts for low‐temperature reverse water‐gas shift (RWGS) reaction. Issue 8 (15th March 2021) - Deng, Lidan; Ai, Xin; Xie, Fengqiong; Zhou, Guilin
Abstract: CO2 hydrogenation for syngas can alleviate the pressure of un‐controlled emissions of CO2 and bring enormous economic benefits. Advantageous Ni‐catalysts have good CO2 hydrogenation activity and high CO selectivity merely over 700 °C. Herein, we introduced Cu into Ni catalysts, which were evaluated by H2 ‐TPR, XRD, BET, in‐situ XPS and CO2 ‐TPD, and their CO2 hydrogenation activity and CO selectivity were significantly affected by the Ni/Cu ratios, which was rationalized by the synergistic effect of bimetallic catalysts. In addition, the reduction temperatures of studied catalysts apparently affected the CO2 hydrogenation, which were caused by the number and dispersion of the active species. It's found that the Ni1 Cu1 ‐400 had good stability, high CO selectivity (up to 90%), and fast formation rate (1.81×10 −5 mol/gcat /s) at 400 °C, which demonstrated a good potential as a superior catalyst for reverse water‐gas shift (RWGS) reaction. Abstract : The hydrogenation of CO2 towards CO is realized with good selectivity and reactivity by using the bimetallic Ni1 Cu1 ‐400 due to the synergistic effect between Ni and Cu, which shows good potential as a superior catalyst for low‐temperature RWGS reaction.